2014
DOI: 10.1016/j.porgcoat.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-oxidative aging of epoxy coating systems

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. a b s t r a c tThe thermo-oxidative behavior of unformulated (unfilled) samples of epoxy coatings has been studied at five temperatures ranging from 70• C to 150• C. Two epoxy networks based on diglycidyl ether of bisphenol A (DGEBA), respectively, cured by jeffamine (POPA) or polyamidoamine (PAA) were compared. Infrared spectrophotometry (IR), differential sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…where A l is the absorbance, l the thickness of the film (expressed in cm), c the concentration (in mol l À1 ) and ε l the molar absorptivity at the considered wavenumber (in l mol À1 cm À1 ). Concentrations of oxidation products were thus assessed using molar absorptivity values equal to 500 l mol À1 cm À1 for carbonyls at 1765 cm À1 in PKHJ (estimated from phenyl acetate e see Appendix 1), 680 l mol À1 cm À1 for carboxylic acids at 1730 cm À1 in TGMDA-DDS [23] and 470 l mol À1 cm À1 for amides at 1675 cm À1 [10] (NB: the nature of the products will be justified later). Some comparisons were performed with the oxidation of TGMDA and DGEBA monomers.…”
Section: Characterizationmentioning
confidence: 99%
“…where A l is the absorbance, l the thickness of the film (expressed in cm), c the concentration (in mol l À1 ) and ε l the molar absorptivity at the considered wavenumber (in l mol À1 cm À1 ). Concentrations of oxidation products were thus assessed using molar absorptivity values equal to 500 l mol À1 cm À1 for carbonyls at 1765 cm À1 in PKHJ (estimated from phenyl acetate e see Appendix 1), 680 l mol À1 cm À1 for carboxylic acids at 1730 cm À1 in TGMDA-DDS [23] and 470 l mol À1 cm À1 for amides at 1675 cm À1 [10] (NB: the nature of the products will be justified later). Some comparisons were performed with the oxidation of TGMDA and DGEBA monomers.…”
Section: Characterizationmentioning
confidence: 99%
“…However, those phenomena were mainly evidenced in rigid epoxy/diamine systems where 2hydroxypropyl ether is possibly the only reactive site. The case of flexible epoxies (T g < 100 C) [18,19] was more scarcely studied so that we were interested in investigating:…”
Section: Introductionmentioning
confidence: 99%
“…The formation of carbonyl group arises from the oxidization of the secondary alcohol groups in epoxy thermoset, 39 whereas that of amide group originates from oxidation of the a-amino carbon belonging to the chain segments. 40 As the temperature exceeds 500 8C, the typical absorption peaks at 1609, 1509, and 1460 cm 21 due to C@C stretching vibration in aromatic ring vanish, whereas a new broader peak at 1594 cm 21 shows up, manifesting the formation of polyaromatic structures. 41,42 In the case of EP/DAP10 and EP/AP10, it can be found that in the range of 25 to 500 8C, the spectra are similar to those of neat EP.…”
mentioning
confidence: 98%